Cytokines Driven Anti-Inflammatory and Anti-Psoriasis Like Efficacies of Nutraceutical Sea Buckthorn (Hippophae rhamnoides) Oil - Balkrishna, Acharya; Sakat, Sachin Shridhar; Joshi, Kheemraj; Joshi, Kamal; Sharma, Vinay; Ranjan, Ravikant; Bhattacharya, Kunal; Varshney, Anurag (Frontiers in Pharmacology, 2019)
Psoriasis is a chronic inflammatory skin disease characterized by circumscribed, red, thickened plaques with an overlying silvery white scales. It is associated with the release of pro-inflammatory mediators that lead to the development of edema and distress. Here we show, the anti-inflammatory and anti-psoriatic efficacies of a neutraceutical Seabuck thorn oil (SBKT) derived from the fruit pulp of Hippophae rhamnoides. Chemical analysis of the SBKT showed the presence of sixteen major saturated, mono- and poly-unsaturated fatty acids components, imparting significant nutritional values. Efficacy of the SBKT in modulating psoriasis and associated inflammation were first tested in-vitro using human monocytic (THP-1) cells. SBKT induced cytotoxicity at the dose of ≥25 μL/mL. Treatment of the LPS-stimulated THP-1 cells with SBKT subdued the enhanced release of intracellular reactive nitrogen species (RNS) and expression of NF-κB protein, in a concentration-dependent manner. This was accompanied by a reduction in the release of downstream pro-inflammatory cytokines: Interleukin (IL)-1β and IL-6. Tumor Necrosis Factor-alpha releases in the stimulated THP-1 cells was also inhibited at SBKT dose of 5 μL/mL. In-vivo oral and topical treatment with SBKT in the Carrageenan stimulated Wistar rats, showed a significant decrease in inflammation-induced paw volume increase and edema. In the 12-O tetradecanoyl phorbol 13-acetate stimulated CD-1 mice psoriasis like model, concurrent oral and tropical SBKT treatments substantially reduced ear edema and ear biopsy weights. Histopathologically, significant reduction in ear epidermal thickness and skin lesion scores were observed in the SBKT treated animals. In conclusion, SBKT showed anti-inflammatory and anti-psoriasis like efficacies in healing drug-induced inflammation and psoriasis. Mode of action of SBKT was found through inhibition of RNS; and down-regulation of NF-κB protein and pro-inflammatory cytokines. Thus, the presented data suggest that SBKT can be used as an anti-inflammatory and anti-psoriatic nutraceutical product.